Peningkatan produktifitas proses produksi sampul raport melalui teknologi tepat guna - Zuliyati Zuliyati; Edwin Djoenaedi; Hutomo Rusdianto (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
The purpose of this activity is the empowerment of small industries, especially in the cover craftsmen and report cards “GiGa” as service partners. The method used is technology guidance through the application of appropriate technology, assistance in the use of multi-use press machines using hydraulic, e-commerce, financial administration and management assistance. The precise technology of a multipurpose automatic press machine with a hydraulic machine can be used to produce a wide range of quality cover products with an effective and efficient production system. The results of this activity are increasing the ability of independent and resilient partners and increasing the role of the micro industry in development, creating job opportunities, increasing income for cover and report card craftsmen “GiGa”  in particular and the country in general, thus realizing a better economy. The output of this activity is an automatic multi-use press machine using hydraulic, effective and efficient production processes, quality cover products.